Microscopic and Cytological Examination of Hyperchromatic Crystalline Deposits in Phacolytic Glaucoma - Murat Hasanreisoğlu; Kübra Serbest Ceylanoğlu; Nuriye Gökçen Yalçın; Pınar Uyar Göçün; Zeynep Aktaş (Türk Oftalmoloji Dergisi, 2014)
Presence of iridescent particles is a well-known clinical condition in phacolytic glaucoma patients with severe high intraocular pressure. Several articles stated that hyperchromatic crystalline deposits were cholesterol crystalline deposits. However, some articles focus on the possible oxalate content of the hyperchromatic crystalline material. Nevertheless, there are few articles which provide information about these crystalline structures at the microscopic level. The purpose of this manuscript was to report the case of a phacolytic glaucoma patient with intense crystalline accumulation in the anterior chamber and to present the microscopic features of these crystalline deposits. (Turk J Ophthalmol 2014; 44: 490-2)